Tomato saponin supplementation ameliorates the development of experimental arthritis by regulating inflammatory responses. (October 2018) - Yoshikawa, Yuko; Katayanagi, Yuki; Kamiya, Manatsu; Yamamoto, Yuri; Fukutomi, Ryuta; Imai, Shinjiro; Miyoshi, Noriyuki; Ohashi, Norio
Graphical abstract: Highlights: Esculeoside A is a major saponin found in Japanese pink-colored tomato. Arthritis was ameliorated by the ingestion of tomato saponin including esculeoside A. This anti-arthritis activities would be mediated by Th1 inhibition and Th2 activation. Aglycon of esculeoside A is a characteristic factor to inhibit inflammation in vitro. Abstract: We evaluated the effect of tomato saponin, containing esculeoside A, a major saponin found in Japanese pink-colored tomato, on collagen-induced arthritis DBA/1J mice. Arthritis scores in collagen-injected mice were markedly lower by tomato saponin supplementation than that of the control throughout the 15-days observation period. Notably, there was a significant negative correlation between the arthritis scores and serum concentrations of esculeogenin A, an aglycon of esculeoside A (R 2 = 0.84, p < 0.05). Additionally, mRNA expression of pro-inflammatory cytokines in the knee joint were significantly decreased by tomato saponin. Moreover, CD38 + CD45R + splenocytes were significantly increased by tomato saponin, suggesting the shift to the type II helper T cell (Th2) response. In cultured splenocytes from DBA/1J mice, purified esculeogenin A also significantly suppressed the lipopolysaccharide-induced IL-12p40, Th1-driving component, and pro-inflammatory cytokines. Our results suggest that esculeogenin A potentially ameliorates collagen-induced arthritis by inhibiting the pro-inflammatory cytokines involved in the activation of Th1.